A review of natural fiber composites: Extraction methods, chemical treatments and applications. (2021) - Sathish, S.; Karthi, N.; Prabhu, L.; Gokulkumar, S.; Balaji, D.; Vigneshkumar, N.; Ajeem Farhan, T.S.; AkilKumar, A.; Dinesh, V.P.
Abstract: Developing sustainable products from renewable materials represents a large dispute in the last few years. Bio-fibers obtained by retting process from plants are receiving more attention from material experts owing to their sustainability, bio degradability, renewability and recyclability nature. The physical and mechanical properties of natural fibers depend on the cultivation method, environmental condition, extraction method and microfibrillar angle. Plant fibers are separated either by dew retting, water retting and/or mechanical decortications method. The properties of natural fiber reinforced composites could be enhanced by suitable chemical treatment processes. This literature survey proposes an in depth review of the extraction methods, chemical treatments and applications for natural fiber composites. We recapitulate the conclusion from the various recent literatures and the chemical treatment outcomes on the mechanical performance of the natural fibers are being highlighted.